Performance Improvement of Membrane Stress Measurement Equipment through Evaluation of Added Mass of Membrane and Error Correction - Sang-Wook Jin; Hiroshi Ohmori; Seungjae Lee (Shock and Vibration)
One of the most important issues in keeping membrane structures in stable condition is to maintain the proper stress distribution over the membrane. However, it is difficult to determine the quantitative real stress level in the membrane after the completion of the structure. The stress relaxation phenomenon of the membrane and the fluttering effect due to strong wind or ponding caused by precipitation may cause severe damage to the membrane structure itself. Therefore, it is very important to know the magnitude of the existing stress in membrane structures for their maintenance. The authors have proposed a new method for separately estimating the membrane stress in two different directions using sound waves instead of directly measuring the membrane stress. The new method utilizes the resonance phenomenon of the membrane, which is induced by sound excitations given through an audio speaker. During such experiment, the effect of the surrounding air on the vibrating membrane cannot be overlooked in order to assure high measurement precision. In this paper, an evaluation scheme for the added mass of membrane with the effect of air on the vibrating membrane and the correction of measurement error is discussed. In addition, three types of membrane materials are used in the experiment in order to verify the expandability and accuracy of the membrane measurement equipment.